THE STUDENTS’ PROFILE IN READING COMPREHENSION OF THE NINTH GRADE JUNIOR HIGH SCHOOLS IN SINGARAJA IN THE ACADEMIC YEAR 2012/2013 - ., I PUTU MARIANA; ., Prof. Dr. Putu Kerti Nitiasih, MA; ., Dr. I Gede Budasi,M.Ed,Dip.App.Lin (Jurnal Pendidikan Bahasa Inggris Indonesia, 2013)
This study aimed at describing the students? profile in reading comprehension of the ninth grade in five junior high schools in Singaraja which is described from five dimensions, namely; 1) general or main idea, 2) certain information or details or implied information, 3) word reference, 4) word meaning, and 5) communicative purpose used in the text. The obtained data were analyzed using descriptive method. Based on the findings of this study, it could be concluded that the students? profile in determining the general or main idea of the text was categorized as instructional level because they got average score of 50. The students got average score 50.47 in determining certain or details or implied information of the text which was categorized as instructional level. In determining word reference, the students? profile was categorized as independent level because they got average score of 60. The students got average score determining word meaning 40. It was categorized as instructional level. In determining communicative purpose, the students? profile was categorized as independent level because they got average score of 40.keyword : students? profile, reading comprehension